(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2019)
Pulau Salah The name is also called Banjar Island is located in Banyuasin 1 Kelurahan Mariana Ilir Sungai Musi Sumatera Selatan. Area of Island Salah Name about 170 ha. Phytoplankton is one of the parameters of water fertility. Algae or phytoplankton can act as one ecological parameter that can describe the condition of a waters and is also an important biotic component in the metabolism of water bodies, since it is the primary link in the food chain of aquatic ecosystems. The purpose of the study was to provide information on the composition, abundance and diversity of phytoplankton in South Sumatra’s Wrong Island. The research was conducted on Pulau Salah Nama, sampling was conducted in 5 stations. The study was conducted in August 2016, November 2016 and January 2017. The study found 3 classes of phytoplankton namely Bacillariophyceae, Chlorophyceae and Cyanophyceae. The highest composition is found in the Bacillariophyceae class. The abundance of phytoplankton ranges from 4.2 Ã— 10 3 cells / l to 2,34 Ã— 10 5 cells / l. The phytoplankton diversity index in Pulau Salah Nama is 0-3 belonging to category 1 <H ’<3 is said to be the stability of the moderate biota community.